Quentin Letesson and Carl Knappett (eds). Minoan Architecture and Urbanism. New Perspectives on an Ancient Built Environment. - Wiersma, Corien (Journal of Greek Archaeology, 2018)
The volume under discussion arises from a workshop held at the University of Toronto in 2015, entitled ‘From Static Data to Dynamic Processes: New Perspectives on Minoan Architecture and Urbanism’. It consists of 15 chapters, which are preceded by a list of figures, tables and contributors. A brief index can be found at the back. References are listed at the end of each individual chapter.